Case Study: The Application of Laughter Therapy in Type II Diabetes Mellitus Patients for Blood Glucose Instability - Wahyu Dwi Ari Wibowo; Roni Roni; Sapondra Wijaya; Yoan Rosa Tiara; Bambang Soewito, Soewito (Indonesian Journal of Global Health Research, 2024)
Elevated blood glucose levels in type II diabetes mellitus (DM) can cause serious organ damage. In Indonesia, the prevalence of DM is increasing, with many patients not receiving adequate treatment. Non-pharmacological therapies, such as laughter therapy, are considered effective in reducing blood glucose levels and stress, especially in elderly patients with type II DM. Research Objective: To describe the outcomes of implementing laughter therapy nursing care in type II DM patients with the nursing problem of blood glucose instability in the working area of Citra Medika Health Center, Lubuklinggau, in 2024. Research Method: A case study method involving two individuals with a medical diagnosis of type II DM, utilizing family nursing care, and implementing laughter therapy over four sessions in one week, with a duration of 20-30 minutes each session. Research Results: Subject I experienced a decrease in random blood glucose levels from 189 mg/dl on the first day to 83 mg/dl on the fourth day. Subject II experienced a decrease from 237 mg/dl on the first day to 116 mg/dl on the fourth day. The difference in reduction between the two subjects was influenced by factors such as family support, the use of hyperglycemia medication, and diet control. Conclusion: The application of laughter therapy can reduce blood glucose levels in patients with type II DM. Further research should include the control of independent repeated actions, the use of diabetes medication, and a larger number of respondents. Suggestions: Laughter therapy can be used as a complementary therapy in the management of type II DM in older adults.